Python Artificial Intelligence Projects for Beginners : Get up and Running with Artificial Intelligence Using 8 Smart and Exciting AI Applications. - Eckroth, Joshua (Packt Publishing Ltd, 2018)
This book demonstrates AI projects in Python covering modern techniques that make up the world of Artificial Intelligence. You will come across a variety of real-world projects on classifying data, text processing techniques, deep learning and neural networks.